Eating Disorder Attitudes and Body Self-Image of Urban Mediterranean Adolescents - Francisca Sempere-Ferre; Dolores Escrivá; Jordi Caplliure-Llopis; Inmaculada Benet; Carlos Barrios (Children, 2023)
Background: Early detection tools for eating disorders play an essential role in their prevention. The aim of this study was to analyze different variables associated with the risk of eating disorders and their relation to anthropometric parameters, nutritional status and body self-image. Methods: The Eating Disorder Invetory-3 Referral Form (EDI-3 RF) and the Body Shape Questionnaire (BSQ) were administered to 809 adolescents (413 boys and 396 girls), aged 11 to 17 years, from three randomly chosen schools in a big Mediterranean city. Anthropometric measurements were taken following standardized methods. Overweight and obesity were determined according to the International Obesity Task Force (IOTF). Results: Overweight (23%) prevailed over obesity (9.37%). Girls registered a higher score in the Obsession for Thinness EDI-3 RF subscale and in the body dissatisfaction section of the BSQ. The only statistically significant differences in the Obsession for Thinness and Body Dissatisfaction levels among the different ages were seen in boys. In this series, body dissatisfaction assessed by the EDI-3 RF was not correlated with BSQ body dissatisfaction. Sex and age in adolescence determine the relationship between eating disorder attitudes and body shape dissatisfaction. Conclusions: It is necessary to look for other parameters to investigate to determine body dissatisfaction.